Relationship between white matter integrity and post-traumatic cognitive deficits: a systematic review and meta-analysis. Issue 1 (2nd August 2018) - Zhang, Jie; Tian, Liang; Zhang, Li; Cheng, Ruidong; Wei, Ruili; He, Fangping; Li, Juebao; Luo, Benyan; Ye, Xiangming
Abstract : Objective: To investigate relationships between cognitive domains and white matter changes in different regions in patients with cognitive deficits after traumatic brain injury (TBI). Methods: Databases including PubMed, Embase, Web of Science and CENTRAL were searched for studies published before 5 August 2017. Correlation coefficients between cognition and white matter integrity, measured by diffusion metrics, including fractional anisotropy (FA), were pooled from 49 studies including 1405 patients. The influence of demographic factors was assessed by meta-regression analysis. Results: Significant pooled FA–executive correlations (p<0.001) were found across various regions, including the corpus callosum (CC) (r=0.42, 95% CI 0.30 to 0.54), superior longitudinal fasciculus (r=0.50, 95% CI 0.41 to 0.59) and internal capsule (IC) (r=0.49, 95% CI 0.37 to 0.61). The fornix (r=0.62, 95% CI 0.45 to 0.78) and cingulum (r=0.57, 95% CI 0.34 to 0.81) particularly correlated with memory (p<0.001). The CC and IC also showed significant relationships with attention and processing speed (p<0.001). Demographic factors had no influence overall, except that studies with a greater proportion of males had stronger correlations between memory and white matter (p<0.05). Conclusions: FA is the most sensitive metric for detecting post-TBI cognitive decline across various domains. Representative white matter regions, such as the CC and IC, perform better than whole-brain white matter for reflecting a wide range of cognitive domains, including memory, attention and executive functions. Moreover, the fornix and cingulum particularly reflect memory function. They yield insights into particular imaging indicators that have neuropsychological value.